Routledge companion to sport and exercise psychology global perspectives and fundamental concepts - Papaioannou, Athanasios G.; Hackfort, Dieter (International perspectives on key issues in sport and exercise psychology, 2016)
"Written by an international team of expert contributors, this unique global and authoritative survey explores in full but accessible detail the basic constructs and concepts of modern sport and exercise psychology and their practical application. The book consists of over 70 chapters, arranged in nine cohesive sections: sport and exercise participants; the influence of environments on sport and exercise; motor skills; performance enhancement; building and leading teams; career, life skills and character development; health and well-being enhancement; clinical issues in sport psychology; and professional development and practice. Each chapter contains chapter summaries and objectives, learning aids, questions, exercises and references for further reading. Its comprehensive scale and global reach make this volume an essential companion for students, instructors and researchers in sport science, sport and exercise psychology, psychology, and physical education. It will also prove invaluable for coaches and health education practitioners"--Provided by publisher.